NUMERICAL SIMULATION OF ADDED MASS FORCE AND PRESSURE GRADIENT FORCE TO PREDICT THE DEPOSITION PROCESS OF PARTICLES AND THE DISTRIBUTION OF WATER VELOCITIES IN SEWERAGE PIPELINES - MERROUCHI, Farida; FOURAR, Ali; MASSOUH, Fawaz; LAKHDARI, Somia; ZEROUAL, Abdelatif (GeoScience Engineering, 2025)
The dispersion and deposition of solid particles in turbulent flows within sewer networks were numerically analyzed. Given the high density ratio between solid particles and water (greater than 0.1), observed in the semi-arid regions of Algeria, the added mass forces and pressure gradient were integrated into the particle motion equation. A coupled Euler-Lagrange approach, based on the k–w–SST turbulence model and the Discrete Random Walk (DRW) model, was used to simulate fluid flow and particle transport, as well as their interaction with turbulence. The pressure gradients from the numerical simulations of turbulent flow were compared with experimental data from the Dyn-Fluid laboratory at ENSAM Paris, showing excellent agreement. The simulations revealed that pressure drop increases with particle size and higher flow velocities. They also showed that particle deposition rates correspond to known deposition zones in sewer networks, and that an increase in water velocity reduces particle deposition, in line with scientific literature.